Analysis of Factors Affecting the Quality of Internal Audit - Eni Nurhaedin; Srihadi Winarningsih; Devianti Yunita Harahap (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
The role of state-owned enterprises (BUMN) to provide contribution to the growth of the economy in which case it will impact on the improvement of the welfare of the people of Indonesia. One of the of the role of internal auditors who are qualified are participating as well as provide assistance to the company to minimize the errors that may occur. This study re-tested the factors - factors that affect the quality of internal audit. The research method uses descriptive verification method with quantitative approach. Samples of research this is Internal Auditors and Committee on Audit in the BUMN office center r in West Java. The type of data used in this study is the primary data source in the questionnaire form. Research is using path analysis to test the construct paths are tested by empirical or not. The data were processed using the Statistical Package for Social Sciences (SPSS) program. Results of the study showed that objectivity is not influenced positive in significant the quality of Internal Audit, Integrity and Competence are partially influenced positive in significant to the quality of Internal Audit. And simultan there is influence positively in significant from Objectivity, Integrity and Competence of the Quality of Internal Audit.